2020
DOI: 10.13057/ijap.v10i2.34984
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Doping Nikel dan Suhu Sinter pada Pembuatan Kawat Superkonduktor Magnesium Diborida

Abstract: <p class="AbstractText">Peningkatan sifat superkonduktor MgB2 melalui penambahan doping telah banyak dilakukan<em>. </em>Meskipun begitu<em>, </em>pembuatan kawat superkonduktor MgB2  belum secara optimal dihasilkan akibat porositas yang terbentuk dari struktur lapis MgB2. Tujuan penelitian ini adalah untuk menganalisis efek penambahan doping nikel terhadap nilai kristalinitas dan kepadatan serta temperatur optimum dalam sintesis kawat superkonduktor berbasis MgB2. Variabel proses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…This study used SS 304 steel tubes which were cheaper than other metal tubes. The previous characterization also showed that the SS tube did not react with MgB2 when heated [4]. Only a little research has been done to quantitatively characterize the crystallographic texture of MgB2 superconducting wire, in addition to the frequency of publication topics that are not too high.…”
Section: Introductionmentioning
confidence: 99%
“…This study used SS 304 steel tubes which were cheaper than other metal tubes. The previous characterization also showed that the SS tube did not react with MgB2 when heated [4]. Only a little research has been done to quantitatively characterize the crystallographic texture of MgB2 superconducting wire, in addition to the frequency of publication topics that are not too high.…”
Section: Introductionmentioning
confidence: 99%